PREVALENCE OF BRUCELLOSIS IN SHEEP IN CAUVERY DELTA REGION OF TAMIL NADU - L. Sowmiya; A. Sangeetha; S. Balakrishnan; N. Arunmozhi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was aimed to assess the seroprevalence of brucellosis in sheep of Cauvery Delta region by collecting serum samples from apparently healthy sheep and sheep with the history of abortion. Serum samples from a total of about 123 animals including 64 from apparently healthy animals, 54 from animals with previous history of abortion and 5 from aborted animals were subjected to serological tests like Rose Bengal Plate Test (RBPT), Standard Plate Agglutination Test (SPAT) and indirect Enzyme Linked Immuno-sorbent Assay (i-ELISA). Molecular identification was carried out with the aborted materials from 5 animals with Bcsp31 gene. The prevalence rate of Brucellosis was 26.01 %, 22.76 % and 41.46 % by RBPT, SPAT and i-ELISA respectively. Among the 5 aborted animals, two were found to be positive for brucellosis with all the four diagnostic tests. Among the three serological tests, the highest seroprevalence of 41.46 % was observed when i-ELISA was used. However, RBPT was considered to be cost effective and easy to test. Hence, from this study it can be concluded that periodical screening of animals with cost effective serological tests for diseases like brucellosis, which is of economic and public health significance is mandatory to prevent the disease outbreak and economic loss to thefarmers.